Indonesia’s Energy Development: Evaluation of the 2015-2019 Medium Term Development Plan and Outlook for that of 2020-2024 - Hanan Nugroho (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2019)
The paper presents the performance of energy development programs during the 2015-2019 RPJMN period, evaluates them, and proposes some recommendations for that of the next 2020-2024 RPJMN. Energy development programs in the 2015-2019 RPJMN performed quite well, however some indicators such as coal production and the share of new-new and renewable energy in the country’s energy mix were not encouraging. While most of energy infrastructure program was not delivered well, the oil and gas production declining trends, in addition to excessive exports of coal reminds that Indonesia’s energy security is not safe. In 2020-2024 RPJMN exploration efforts must be increased, aiming at achieving reserves replacement ratio more than 1. Meanwhile, the share of new and renewable has to be increased, by emphasizing the development of biofuels in particular. In addition, energy conservation efforts have to be continued.